2013
DOI: 10.1097/iae.0b013e31825e1d62
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Sclerotomy-Related Retinal Breaks During 23-Gauge Pars Plana Vitrectomy

Abstract: Pars plana vitrectomy (23-gauge) is associated with a low incidence of sclerotomy-related retinal breaks and postoperative retinal detachments. Eyes with breaks are more likely to be phakic and without a preoperative posterior vitreous detachment. The presence of vitreomacular traction may be a risk factor for the development of intraoperative sclerotomy-related breaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
1
29
1
1
Order By: Relevance
“…10,[22][23][24][25][26][27][28][29][30][31][32] After NVS, Saito et al 5 reported no retinal breaks during the follow-up period. In our study, similar incidence of retinal breaks in two groups suggests that NVS does not negatively affect the retina.…”
Section: Discussionmentioning
confidence: 99%
“…10,[22][23][24][25][26][27][28][29][30][31][32] After NVS, Saito et al 5 reported no retinal breaks during the follow-up period. In our study, similar incidence of retinal breaks in two groups suggests that NVS does not negatively affect the retina.…”
Section: Discussionmentioning
confidence: 99%
“…The reports available in the literature vary widely: the incidence of intraoperative RBs reported ranges from 0% to 24%, and that of postoperative RRD ranges from 0% to 16%. 123 These differences might be explained by the way the patients were selected. Some investigators evaluate the incidence of exclusively intraoperative breaks located in the periphery, 3,11 whereas others include only those caused by the induction of posterior vitreous detachment (PVD), 4,10 and still others only sclerotomy-related breaks.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators evaluate the incidence of exclusively intraoperative breaks located in the periphery, 3,11 whereas others include only those caused by the induction of posterior vitreous detachment (PVD), 4,10 and still others only sclerotomy-related breaks. 23 The surgical technique used may also have an impact on this variation. 116 A further parameter that may affect the development of RB and RRD is the choice of instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Tous les facteurs dépendants du chirurgien tendent à diminuer avec l'expérience. Enfin, plusieurs études ont montré que la réalisation d'une vitrectomie transconjonctivale 23-ou 25-gauge entraînait une réduction des déchirures peropératoires et des DR postopératoires par le biais de la réduction des tractions et de l'incarcération du vitré dans les sclérotomies [9,10].…”
Section: Identification Des Facteurs De Déchirures Rétiniennes Liés àunclassified